Tracing Lines in Sand. (30th May 2018) - Fisk, Anna; Vincent, Alana M
Abstract: The guest editors introduce the Special Issue, 'Lines in Sand: Borders, Conflicts and Transitions'. The articles in this issue all originated as presentations at the 18th Biennial Conference of the International Society for Religion, Literature and Culture, held at the University of Glasgow, 9–11 September 2016.